1993
DOI: 10.1017/s0263574700019421
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical concept of the neurosurgical robot ‘Minerva’

Abstract: We describe a robot capable of performing all procedures necessary to carry out a complete stereotactic neurosurgical operation under the control and supervision of a surgeon. The operation consists of the introduction of a small probe with diameter 2–3 mm through a hole without trepanation. The robot has been built and is now being tested and evaluated. The accompanying control software as well as various medical probes are either in development or partially tested. The installation will be able to carry out … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

1995
1995
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(9 citation statements)
references
References 1 publication
0
7
0
2
Order By: Relevance
“…Due to the limited work envelope of the system and control algorithms, a preliminary study on healthy subjects indicated that walking speeds on the simulator were significantly slower than normal over-ground walking. 7 A fracture of the lower tibia which affects the internal (medial) and external (lateral) malleolus A parallel manipulator robot was implemented on a traction table by Lin et al [127] for a femoral fracture reduction in a clinical environment. In the clinical setup, the patient is positioned on the traction table with a flexed knee.…”
Section: Parallel Robot For Medical Applicationsmentioning
confidence: 99%
“…Due to the limited work envelope of the system and control algorithms, a preliminary study on healthy subjects indicated that walking speeds on the simulator were significantly slower than normal over-ground walking. 7 A fracture of the lower tibia which affects the internal (medial) and external (lateral) malleolus A parallel manipulator robot was implemented on a traction table by Lin et al [127] for a femoral fracture reduction in a clinical environment. In the clinical setup, the patient is positioned on the traction table with a flexed knee.…”
Section: Parallel Robot For Medical Applicationsmentioning
confidence: 99%
“…In neurosurgery, three broad types of devices have been developed to improve spatial accuracy and surgical precision: neuronavigators, stereotactic localizers, and robotic assistants. [1][2][3] In orthopedic surgery, robots that cut or ream bone provide similar advantages. 1 The success of robots in neurosurgery and orthopedic surgery has encouraged the investigation of robots in other surgical specialties, including urology.…”
Section: Introduction Wmentioning
confidence: 99%
“…The mechanical design of this system was presented by Glauser et al 12 The system consists of a five-degree-of-freedom structure with two linear axes (vertical and lateral), two rotary axes (moving in a horizontal and vertical plane), and a linear axis (to move the tool to and from the patient's head). The robot is mounted on a horizontal carrier which moves on rails.…”
Section: Minervamentioning
confidence: 99%